Numerical Simulation of Flood Routing through Channels with Area Variation using Staggered Grid Method - Bambang Agus Sulistyono; Samijo; Aan Nurfahrudianto; Dian Devita Yohanie; Aprilia Dwi Handayani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
In the event that the discharge goes to enter the channel surpasses the channel ability, than would happen floods of genuine harm to the environment around the channel. Applying the dynamic wave model, the discharge amount could be predicted in the frequent flood region if the information of discharge upstream is found out. Many numerical schemes could be utilized to discover answers to the system of differential partial equations. We proposed the usage of the staggered method to find out the solution of the system. The numerical scheme shall be used to predict the top discharge in a frequent flood region and create a flooded pocket to diminish the top discharge in the region. Based on the outcome of the numerical simulation, we may claim that a stable scheme has been created to acquire the approach resolve of the equation partial system. The staggered scheme is capable of investigating the impact of the presence of the flood pocket especially lessening the top discharge.